Three Essays on the Impact of Climate Change Performance: Evidence from Australia - Alshahrani, Faisal Ahmed S (Curtin University, 2023)
This thesis comprises three essays that examine the association between climate change disclosure performance and financial distress, audit fees, and firm risk.